2013
DOI: 10.1111/petr.12158
|View full text |Cite
|
Sign up to set email alerts
|

Basiliximab with delayed introduction of calcineurin inhibitors as a renal‐sparing protocol following liver transplantation in children with renal impairment

Abstract: Renal impairment is frequently compromised in patients with end-stage liver disease and is associated with increased long-term mortality post-LT. In contrast to CNI, basiliximab is an immunosuppressive agent with minimal nephrotoxic potential. This study reviews the experience of a single pediatric liver transplant center's renal-sparing approach with the use of basiliximab and MMF to compensate for delayed entry of CNI in children with renal impairment at the time of organ availability. There were no differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
(25 reference statements)
2
20
0
Order By: Relevance
“…In this study, the major differences between the two immunosuppressive protocols for perioperative management were the application of basiliximab and thereafter a delay of tacrolimus, granting extra time for the recovery or stabilisation of renal function. The protocols are consistent with previous studies with basiliximab administration, which allow for a delay in initiation and a lower dosage of tacrolimus in both adult and child LT, could preserve renal function for LT recipients, without an unfavourable effect on the complication incidence . Therefore, it was demonstrated that basiliximab is effective in sparing renal function without increasing the incidence of rejection and infection.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, the major differences between the two immunosuppressive protocols for perioperative management were the application of basiliximab and thereafter a delay of tacrolimus, granting extra time for the recovery or stabilisation of renal function. The protocols are consistent with previous studies with basiliximab administration, which allow for a delay in initiation and a lower dosage of tacrolimus in both adult and child LT, could preserve renal function for LT recipients, without an unfavourable effect on the complication incidence . Therefore, it was demonstrated that basiliximab is effective in sparing renal function without increasing the incidence of rejection and infection.…”
Section: Discussionsupporting
confidence: 85%
“…Currently, most available studies of basiliximab utilisation in LT were conducted in non-hepatitis B patients, though hepatitis B is still considered to be quite prevalent in China (1,(9)(10)(11)(12)(13)(14). The application of basiliximab focusing on LT recipients with HBVrelated diseases has rarely been investigated around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Basiliximab, a chimeric anti‐interleukin (IL) 2 receptor antibody, has been used in induction of immunosuppression. Its use is associated with a lower incidence of acute cellular rejection and can reduce the use or delay the introduction of CNIs, which is particularly helpful in patients with renal dysfunction …”
Section: Specific Immunosuppressionmentioning
confidence: 99%
“…Its use is associated with a lower incidence of acute cellular rejection and can reduce the use or delay the introduction of CNIs, which is particularly helpful in patients with renal dysfunction. (48)…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
“…All study patients followed institutional protocols for immunosuppression which were largely unchanged during the duration of the study period 23 . Briefly, the standard induction immunosuppression comprised dual therapy with tacrolimus and corticosteroids, with a taper to discontinuation of steroids by 3 months post‐transplant.…”
Section: Methodsmentioning
confidence: 99%